The Nobbie stories for children and adults - James, C. L. R. (Cyril Lionel Robert), 1901-1989 (University of Nebraska Press, 2006)
After more than a decade in the United States, the Caribbean writer C.L.R. James ran afoul of McCarthyism in 1953 and was deported. In exile in London, he began to write stories in the form of letters to his four-year-old son "Nobbie," who remained in the States. Through a distinctive, imaginary, and sometimes absurd cast of characters--Good Boongko, Bad boo-boo-loo, Moby Dick, and Nicholas the worker, among others--these stories explore questions of friendship, conflict, community, ethics, and power in humorous and often ingenious ways; they also stand as a moving testament to a father's struggle to be a vivid presence in the life of his son despite separation and distance.